Fake news circulation on social media and the need for a policy evolution in India. (10th November 2020) - Patra, Raj Kishore; Saha, Arpita
Upsurge of the social media and the ubiquity of fake news have been the common phenomena, which negatively affects the spirit and ethics of journalism profession. The policies of the social media giants are inadequate to challenge this menace. Also, the existing legal and regulatory bodies are barely equipped to counter the vicious circle. There are frail and inadequate public policies to monitor this progressive dysfunction of media. The paper examines the origin of fake news, its intricacies and the role of social media in circulating fake contents. Further, it highlights the inadequacies of the existing policies to regulate the flow of fake content. The study administers the qualitative method, involving focus group discussions (FGD) with academicians and millennials, and in-depth interviews with industry professionals. Finally, it attempts to examine the purpose of 'misinformation' circulation and enumerates certain guiding principles to frame policies to regulate its exorbitant rise online.